Insights into human melanocyte development and characteristics through pluripotent stem cells combined with single-cell sequencing - Jie Yang; Zihan Wang; Hang Zhou; Yuyun Xiong; Yumei Li; Yun-wen Zheng; Liping Liu (iScience)
Summary: Human pigment-related diseases are closely linked to melanocytes, yet our understanding of their development has largely relied on animal models. The utilization of pluripotent stem cells (PSCs) has shown immense potential in advancing our knowledge of human developmental biology. This study utilized human PSCs and single-cell sequencing to investigate the cellular heterogeneity and dynamic changes in biological characteristics, differentiation trajectory, and signaling interactions during melanocyte development. By integrating datasets from normal human melanocytes, we verified that PSC-derived melanocytes closely resemble normal human melanocytes, especially in early stages. Exploration of cell-cell communication revealed intricate signaling pathways, including Bone Morphogenetic Protein (BMP), Wingless/Integrated (WNT), and transforming growth factor β (TGF-β), in subpopulations of induced melanocytes. Additionally, PDGFRB may serve as a potential surface marker for stemness maintenance in melanocytes. Collectively, these findings demonstrate that PSCs can effectively stimulate human melanocyte development, thereby providing a valuable tool for further investigations into melanocyte-related diseases.